Characterizing the supragingival microbiome of healthy pregnant women - Zhang, Yangyang; Wu, Zeyu; Li, Ling; Wang, Xiaohe; Fan, Wenxian; Zhao, Jin (Frontiers in Cellular and Infection Microbiology, 2022)
The ecological characteristics and changes of the supragingival plaque microbial community during pregnancy are poorly understood. This study compared the microbial community characteristics of supragingival plaque in pregnant and non-pregnant women, with the aim of identifying specific microbial lineages and genera that may be associated with pregnancy. Thirty pregnant women were randomly selected from the First Affiliated Hospital of Xinjiang Medical University and divided into groups based on pregnancy trimester: first trimester (group P1, n=10, ≤12 weeks), second trimester (group P2, n=10, 13–27 weeks), and third trimester (group P3, n=10, 28–40 weeks). Ten healthy non-pregnant women (group N) were enrolled as the control group. Supragingival plaque samples of all subjects were collected and oral microbial composition was surveyed using a 16S rRNA gene sequencing approach. Statistical analysis was performed using a nonparametric test. The Chao 1 index of P3 was significantly lower compared with that of N, P1, and P2 (P<0.05). The Simpson indices of P2 and P3 were significantly higher than that of N (P<0.05). The Shannon index of P2 was significantly higher compared with that of N (P<0.05). Principal coordinate analysis (PCoA) showed different clustering according to the pregnancy status. Linear discriminant analysis effect size (LEfSe) revealed that the microbial species in group N that were significantly different from those of other groups were concentrated in the genus Neisseria. Species in P1 that were significantly different from those of other groups were concentrated in the genus Tannerella, while those in P2 and P3 were concentrated in the genus Leptotrichia. A total of 172 functional pathways were predicted for the bacterial communities in this study using PICRUSt2. Principal Component Analysis (PCA) showed that most predicted functional pathways clustered together in N and P1 and in P2 and P3. LEfSe analysis revealed that 11 pathways played a discriminatory role in the four groups. This work suggests a potential role of pregnancy in the formation of supragingival plaque microbiota and indicates that physiological changes during pregnancy may convert supragingival plaque into entities that could cause harm, which may be a risk factor for maternal health. Furthermore, findings from the study provide a basis for etiological studies of pregnancy-associated oral ecological disorders.